PROPOSED KITCHEN DESIGN FOR COMPLYING ELDERLY NEEDS - Hari Purnomo; Arya Yudhistira (Journal of Industrial Engineering Management, 2021)
29 Million elderly had accidents during 2014, and caused 29 thousand of death in 2016.  Once of the biggest potential risk for elderly is a kitchen. It caused nursing home, needs to be more consent in designing kitchen for elderly. The purpose of this research was to design comfort kitchen for elderly by using design thinking approach. Design thinking utilized voice of customer to made a decision. It has an excessed as prototype redundant test to gain the voice of customers. Based on the customer needs, this research designed a kitchen with some racks near the dishwasher, applied some handrails in several places, sitting place to wash the dish and to cook, applied a food storage. Kitchen designed without any stairs and create a storage to placing the walker. This proposed design was tested by Wilcoxon signed-rank test to prove the differences the new design with the precedence design